Acceptance of Koha Open Source System among Librarians in the Malaysian Academic Libraries: An Exploratory Qualitative Study - Mohideen, Zainab Ajab; Sheikh, Arslan; Kaur, Kiran; Tahira, Muzammil (Taylor & Francis, 2019)
This paper reports on a study that explores the requirements and level of acceptance for the Koha open source software implementation in Malaysian academic libraries. This is a qualitative study based on interviews with system librarians from library application and system divisions in 5 Malaysian universities. The interviews were conducted to understand the technology acceptance, system quality and system information, beliefs and attitude of librarians and to provide insight into a user and open system relations. These factors can be critical in order to understand what may hinder the acceptance of open source systems in Malaysia academic libraries. The findings disclose that the level of acceptance of the Koha open source system among Malaysian librarians is high as they are satisfied with the information quality, system quality and system platform. They have positive intentions to use this system and believe it meets their current and future information needs. The requirements of its implementation are focused on perceived usefulness (technology), attitude toward using (users), and perceived ease of use (system). The subsequent influencing factors are a reflection of Koha system stability and users’ acceptance of this system’s information quality, system quality, librarians’ awareness, satisfaction, user confidence level, support for library standards, highly integrated modules, a web-based solution, intention to use a system, and actual usage of an open-source system. Practical implications include cost savings, outsourced system maintenance, and accessibility of the system after office hours. The Koha open-source system is a new paradigm in system solutions for libraries in Malaysia. The results of the current study are applicable to other library settings. © 2019, © 2019 The Author(s). Published with license by Taylor & Francis Group, LLC.